Impact of job strain and being overweight on middle and senior managers from the manufacturing sector in the Mexican industry - Armenta-Hernández, Oziely; Maldonado-Macías, Aide Aracely; Baez-Lopez, Yolanda; Realyvásquez-Vargas, Arturo (2021)
This research work establishes the relationship between job strain and being overweight among Mexican managers. Recently in Mexico, there has been a sharp increase in work-related diseases and mental health disorders. Furthermore, evidence shows that Mexicans rank top among employees who suffer from stress, yet research on the impact of job strain on the phenomena of obesity and being overweight among such vulnerable job positions in the industrial field is scarce. METHODS:The sample included 170 overweight middle and senior managers from six companies in the Mexican Manufacturing Industry. Cedillo’s Spanish version of the Job Content Questionnaire by Karasek was used, and the Body Mass Index (BMI) was used to characterize an overweight condition. Structural Equations Modelling studied the relationships among variables. RESULTS:Even though, the model shows a power of explanation of 6%(R2 = 0.06), the variable showing the greatest direct effect on the overweight variable is social support, with 21%(p < 0.01, β= –0.21). Regarding the total effects, only two of the four variables studied contributed directly to the overweight variation: the social support variable and the job demand variable. CONCLUSIONS:The results of the model hold a relatively low explanatory power; however, they do show a relationship between the studied variables. Also, the importance of the supervisor and co-workers’ support should be considered when developing organizational strategies for the prevention of work stress and an overweight condition.